The significant effects of UPV MMBM degree in relation with the placement and promotion of bankers in Iloilo City - Boteros, Paulina
In Iloilo City, banks have been sprouting like mushrooms in the past few years. this must mean that banking is a very lucrative business in Iloilo City. With the emergence of several banks in the City, more banks means more career opportunities for bankers and for hopeful bankers. Most fresh graduates of business related courses have been aiming to start a career in this sector. For those who are already bankers, this would mean that they now have other organizations to continue their career but on a higher level of position. These bankers has the comparative advantage over the other hopefuls bankers because they are more experienced and quite adept with the day to day operation of the bank. Competition is everywhere and the bankers are not spared from it. Just like any other organization, banks are quite meticulous in selecting the right person for a given task. This sector operates with a high fiinancial risk everyday and they would need people who are very skillful and accurate in this kind of operation. Wit this predicament, bankers and hopeful bankers knows that they would need an edge from their counterparts to be able to land on a good job or a better position. One important factor in placement and promotion is the educational attainment of the person thus, bankers now know that having a baccalaureate degree is not enough for promotion but having a post graduate degree might be an advantage. Promotion means the advancement of an employee from one position to another with an increase in duties and responsibilities as authorized by law and ususally acompanied by an increase in salary. The possibility of advancements often serves as a major incentive for superior managerial performance, and promotions are the most significant ways to recognize superior performance. therefore, it is extremely important that promotion be fair - based on merit and untainted by favoritism. Still, even fair and appropriate promotions can create a number of problems. On the other end, placement is when the organization decides that they have the right person for the right job. This takes after screening and selection process in recruitment. The organization only decides to hire the person after a series of rigorous test/examinations and training. this is now the beginning of the person's career in that organization. The researhers studied the significant effects of a UPV MMBM degree for bankers in the city of iloilo and aimed to determine if a MMBM degree from UPV, or any masters degree from any university for that matter, is really an important factor in placement or promotion in the banking sector. This tudy specifically dealt with bankers because the researcher noted that most UPV MMBM graduates and students of this degree program are bankers and are/were studying because thay are of the idea that it will make a huge difference when it comes to their promotion in the future or when they apply to other organizations for a higher position. This study generally focused on the MMBM degree as the factor in placement and promotion but it also dealt with the other factors that has affected it such as the working environment and the organization's office policies regarding this subject. The researchers has randomly selected the masters degree holders from among the commercial banks in the city of Iloilo and has come up with the conclusion that for most banks operating in Iloilo City, a post graduate degree is not a tcket for placement or for promotion but the office policy still prevails. The organization's policy on placement and promotion determined whether the person is qualified for the job and not on the basis of his or her educational background and definitely not on the basis on the University where he or she earned the degree. furthermore, most respondents answered that every employee has equal chances of being promoted and every applicant has equal chances of being hired into the organization.